55‐4: Novel Methodology for Reproducibility of OLED Lifetimes and Identification of Killer Impurities. Issue 1 (25th September 2020) - Fujimoto, Hiroshi; Nakamura, Toshimitsu; Nagayoshi, Kaori; Harada, Kentaro; Miyazaki, Hiroshi; Kurata, Takaomi; Kiyota, Junya; Adachi, Chihaya
Abstract : A new method to investigate the influence of vacuum chamber impurities on OLED lifetime is demonstrated. By combining deposition from a novel‐design crucible with in‐situ exposure to impurity sources, and by controlling the amount of water impinging, we show that the influence of water and impurities can be separately examined.